2022
DOI: 10.1002/adma.202203796
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Device Physics of Dilute‐Donor Narrow‐Bandgap Organic Solar Cells with Highly Transparent Active Layers

Abstract: The charge generation–recombination dynamics in three narrow‐bandgap near‐IR absorbing nonfullerene (NFA) based organic photovoltaic (OPV) systems with varied donor concentrations of 40%, 30%, and 20% are investigated. The dilution of the polymer donor with visible‐range absorption leads to highly transparent active layers with blend average visible transmittance (AVT) values of 64%, 70%, and 77%, respectively. Opaque devices in the optimized highly reproducible device configuration comprising these transparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 90 publications
(165 reference statements)
1
37
0
Order By: Relevance
“…As shown in the TEM image of the blend film in Fig. 4i-l, bright and dark regions correspond to regions with different scattering contrasts for donor-rich or acceptor-rich phases [45]. With the decrease in donor content (from 50% to 40%), clear, bright areas were observed in blend films.…”
Section: Morphology Characterization Of Dilute Donor Blendsmentioning
confidence: 85%
See 1 more Smart Citation
“…As shown in the TEM image of the blend film in Fig. 4i-l, bright and dark regions correspond to regions with different scattering contrasts for donor-rich or acceptor-rich phases [45]. With the decrease in donor content (from 50% to 40%), clear, bright areas were observed in blend films.…”
Section: Morphology Characterization Of Dilute Donor Blendsmentioning
confidence: 85%
“…In addition, dilute donor and multicomponent strategies are also golden methods for device optimization on ST-OSCs. For example, Schopp et al [45] reported that the dilute donor increased the average visible transmittance (AVT) of PCE-Th:COTIC-4F active-layer from 63.8% to 69.8%, accompanied by a slight decrease in PCE from 7.0% to 6.5%. In 2021, Hu et al [23] reported a ternary blend with two miscible narrow-bandgap acceptors (Y6-1O and Y6), leading to ST-OSCs with an AVT of 20.2% and a PCE of 13.02%.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the dilute donor approach has been employed by several groups to improve as a platform for increasing the AVT while maintaining a high PCE due to increased IR absorption by a narrow band gap acceptor compound and reduced absorption by a donor compound that absorbs (partially) in the visible range [80,[111][112][113]. In 2021, Yao et al studied PM6:Y6 OPVs with reduced donor content and found an efficiency of over 10% in dilute donor solar cells with only 10 wt% PM6, thanks to efficient charge generation, electron and hole transport, slow charge recombination, and field-insensitive extraction [111].…”
Section: Current Performance and Strategies To Increase Luementioning
confidence: 99%
“…20−23 Nonsolution processes offer the advantage of easy patterning but suffer from nonuniform deposition and difficulty in controlling the resolution/thickness. 5,24 In addition, nonsolution approaches normally involve complicated processing, which offer low compatibility in making flexible electronic devices. Solution processes have attracted increasing research interests in preparing FTEs, and they have shown advantages of mild operation conditions, high throughput, and high capacity in low-cost large-area fabrication.…”
Section: Introductionmentioning
confidence: 99%